Virtual Faculty Development in Simulation in Sub-Saharan Africa: A Pilot Training for Pediatricians in Kisumu, Kenya - Fant, Colleen; Olwala, Macrine; Laanoi, Grace M.; Murithi, Gatwiri; Otieno, Walter; Groothuis, Elizabeth; Doobay Persaud, Ashti (Frontiers in Pediatrics, 2022)
Introduction: Simulation is an effective educational tool increasingly being utilized in medical education globally and across East Africa. Globally, pediatric patients often present with low frequency, high acuity disease and simulation-based training in pediatric emergencies can equip physicians with the skills to recognize and intervene. Northwestern University (NU) in Chicago, IL, USA, and Maseno University (MU), in Kisumu, Kenya launched a predominantly virtual partnership in 2020 to utilize the Jaramogi Oginga Odinga Teaching & Referral Hospital (JOOTRH) simulation center for MU faculty development in simulation based medical education (SBME) for medical students. Materials and Methods: Educational goals, learning objectives, and educational content were collaboratively developed between MU and NU faculty. Virtual sessions were held for didactic education on simulation pedagogy, case development, and debriefing. Mixed educational methods were used including virtual mentored sessions for deliberate practice, piloted case facilitation with medical students, and mentored development of MU identified cases. Trained faculty had the summative experience of an intensive simulation facilitation with graduating MU students. MU faculty and students were surveyed on their experiences with SBME and MU faculty were scored on facilitation technique with a validated tool. Results: There were four didactic sessions during the training. Seven cases were developed to reflect targeted educational content for MU students. Six virtually mentored sessions were held to pilot SBME with MU students. In July 2021, fifty students participated in a week-long SBME course led by the MU trained faculty with virtual observation and mentorship from NU faculty. MU faculty reported positive experience with the SBME training and demonstrated improvement in debriefing skills after the training. The overwhelming majority of MU students reported positive experiences with SBME and endorsed desire for earlier and additional sessions. Discussion/Conclusions: This medical education partnership, developed through virtual sessions, culminated in the implementation of an independently run simulation course by three trained MU faculty. SBME is an important educational tool and faculty in a resource constrained setting were successfully, virtually trained in its implementation and through collaborative planning, became a unique tool to address gaps for medical students. Funding Source: Strohm Family Grant